PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Azis, Citra Ayu Padilah; Suwandi, Memen; Aditiya, Roby (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract, The aim of this research is to determine the effect of corporate social responsibility and capital intensity on tax avoidance with company size as a moderating variable. The data analysis used was hypothesis testing using multiple linear regression and moderation testing using an absolute difference approach. The research results show that corporate social responsibility and capital intensity have a significant positive effect and company size can strengthen the effect of corporate social responsibility on tax avoidance but cannot moderate the effect of capital intensity on tax avoidance in food and beverage sub-sector manufacturing companies in 2020-2022.